Comparison of Upper Central Incisor Torque in the ClinCheck® with and without CBCT Integration: A Cross-Sectional Study - Cíntia Queirós; Maria Gonçalves; Sofia Ferreira; Inês de Castro; Rui M. S. Azevedo; Teresa Pinho (MDPI AG, 2024)
Controlling root movement is one of the greatest challenges in orthodontic treatment with aligners, like Invisalign® aligners. Cone Beam Computed Tomography (CBCT) integration into ClinCheck®, enabling bone and root visualisation, allows a more accurate follow-up of the teeth position. This study aims to compare torque measurements of the upper central incisors with and without CBCT and relate them to the upper incisor inclination and facial biotype. In a sample of 70 teeth, torque measurements were obtained by importing images into AutoCAD® software (version 2024). The angle between the tooth's long axis with CBCT duplicate and the tooth's long axis without CBCT was obtained to assess the difference. Statistically significant differences between torque measurements with and without CBCT were found, as well as between these measurements and the inclination of the upper incisors. No statistically significant differences were found among the facial biotypes. The average values of 27.8° ± 3.4° and 21.5° ± 3.2° were obtained for the angle between the axes. Torque without CBCT was lower than torque with CBCT, for the same tooth. The angle between the axes had a similar mean for both teeth. CBCT integration into ClinCheck® allows for a more correct torque measurement.